Macroeconomic policies, wage developments, and Germany's stagnation - Eckhard Hein; Achim Truger (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2005)
The paper fundamentally challenges the institutional sclerosis explanation of the present German economic stagnation. Instead we present a macroeconomic explanation focusing on the combined effects of too restrictive monetary policies, too restrictive and sometimes pro-cyclical fiscal policies and overly moderate wage policies in Germany since the mid 1990s. This view is broadly consistent with modern macroeconomics and with empirical data. From this perspective we finally argue that Germany urgently needs more expansive fiscal and monetary policies in the short run, and that in the medium run the conditions for nominal wage growth in Germany according to the sum of long run national productivity growth and the ECB's inflation target have to be improved. Further pursuing a policy of structural reforms with respect to the labour market and the social benefit system in combination with a restrictive macroeconomic policy mix, however, will prolong Germany's economic stagnation and will considerably increase the risk of deflation.
urn:nbn:de:101:1-2008081446
Keywords: E63; 330; monetary policy; fiscal policy; structural reform